Selection of Anopheles dirus for refractoriness and susceptibility to Plasmodium yoelii nigeriensis - Somboon P. (2014)
Two lines of the Oriental malaria vector mosquito Anopheles dirus species A (Diptera: Culicidae), one fully refractory and one fully susceptible to Plasmodium yoelii nigeriensis (an African rodent malaria parasite), were established after 17 generations of mass selection, followed by single female selection for one or two generations. Prior to selection, the stock colony of An. dirus was 17% refractory. Both lines of An. dirus produced abundant ookinetes that started to invade the midgut within 24h post-infection, as seen in histological sections. In most of the refractory mosquitoes, oocysts stopped development <12 h post-invasion, indicating a rapid defence mechanism. Dead P. y. nigeriensis parasites were apparently localized as small melanized spots (2-5 microm) seen in wet preparations of mosquito midguts dissected 5-7 days post infective bloodmeal. In some refractory An. dirus females, apart from the spots, a small number of totally encapsulated oocysts (c. 10 microm) were also present. These larger melanized parasites predominated in a few females: they appeared 2-3 days post-infection as a secondary delayed defence mechanism. The progeny of reciprocal matings between susceptible and refractory lines had approximately 50% susceptibility. Backcrosses of F1 hybrids with susceptible or refractory lines increased or decreased the susceptibility of backcross progeny accordingly. Overall, these results suggest polygenic control of susceptibility to P. y. nigeriensis infection. The refractory line of An. dirus showed normal susceptibility to natural infections of the human malarias P. falciparum and P. vivax from local patients.